Al-Shaybānī and Contemporary Renunciant Piety - Melchert, Christopher ca. 20./21. Jh. (Journal of Abbasid Studies, 2019)
Renunciation (zuhd) was a major part of the social and intellectual background of jurists' circles during the formative period of Ḥanafi legal doctrine. Accordingly, the works attributed to Muḥammad b. al-Ḥasan al-Shaybānī (d. 189/804-5) touch on renunciant concerns, especially the incomplete Kitāb al-Kasb (Book of Gain). A discussion of al-Shaybānī's views on renunciation together with comments taken from other renunciant literature shows that, although he affirms some renunciant values, he usually seems to uphold a more world-embracing piety. This puts al-Shaybānī in opposition to a section of the nascent school favouring more extreme forms, such as the repudiation of gain (inkār al-kasb).